2022
DOI: 10.1038/s41698-022-00336-x
|View full text |Cite
|
Sign up to set email alerts
|

The deubiquitinase USP10 protects pancreatic cancer cells from endoplasmic reticulum stress

Abstract: The ubiquitin-specific peptidase 10 (USP10) plays a context-specific, pro or anti-tumorigenic role in different malignancies. However, the role of USP10 in pancreatic cancer remains unclear. Our protein and RNA level analysis from archived specimens and public databases show that USP10 is overexpressed in pancreatic ductal adenocarcinoma (PDAC) and expression correlates with poor overall patient survival. Phenotypically, silencing USP10 decreased viability, clonal growth and invasive properties of pancreatic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Several studies have shown that the accumulation of ubiquitinated proteins induced by deubiquitinase can lead to endoplasmic reticulum (ER) stress and activation of autophagy (Refs 120 , 121 ). Both broad-spectrum inhibitors of deubiquitinases and specific inhibitors of individual deubiquitinases can lead to an increase in the ubiquitination of total proteins, thereby activating ER stress, unfolded protein response and AMPK pathway-mediated autophagy (Refs 122 , 123 ).…”
Section: Deubiquitinase Inhibitors Associated With Cardiac Diseasementioning
confidence: 99%
“…Several studies have shown that the accumulation of ubiquitinated proteins induced by deubiquitinase can lead to endoplasmic reticulum (ER) stress and activation of autophagy (Refs 120 , 121 ). Both broad-spectrum inhibitors of deubiquitinases and specific inhibitors of individual deubiquitinases can lead to an increase in the ubiquitination of total proteins, thereby activating ER stress, unfolded protein response and AMPK pathway-mediated autophagy (Refs 122 , 123 ).…”
Section: Deubiquitinase Inhibitors Associated With Cardiac Diseasementioning
confidence: 99%
“… 115 In pancreatic cancer, USP10 acts to protect cancer cells from apoptosis induced by ER stress. 116 …”
Section: Molecular Functions Of Stress Granules In Cancer Biologymentioning
confidence: 99%